Razvoj družbenih študij znanosti in tehnologije - Mali, Franc (Teorija in praksa, 2013)
The article deals with some aspects of the development of social studies of science and technology at the Faculty of Social Sciences. A presentation is given of the origins of the scientific analysis of science which was initially more philosophically and sociologically oriented and then later gradually redirected towards the interdisciplinary and empirical research paradigm. For that reason, it is today reasonable to talk about the progress made by social studies of science and technology in a broader sense, instead of the sociology of science in a narrow sense. In the context of this development paradigm, most attention in the article is paid to the intellectual sources for the research and teaching of social studies of science and technology at home and abroad, their cognitive and institutional position in the academic world and in society at large. An assessment is made about the possible future development of social studies of science and technology as well.
Keywords: družbene znanosti; Družboslovne študije; Faculty of Social Sciences; Fakulteta za družbene vede; Ljubljana; New technologies; Nove tehnologije; Science; Science policy; Social studies; Sociologija znanosti; Sociology of science; Znanost; Znanstvena politika